Peningkatan Perilaku Inovatif Melalui Penguatan Team Learning dan Knowledge Sharing - Widianti Sudjud; Rais Hidayat; Dian Wulandari (Universitas Pakuan, 2022)
Increasing Innovative Work Behavior Through Strengthening Team Learning and Knowledge Sharing.This study examines the relationship between team learning and knowledge sharing with innovative work behavior. The research was conducted at the Integrated Islamic Elementary School in West Bogor District, Bogor City. The population of this study amounted to 357 teachers. The number of samples was 189 teachers who were determined using proportional random sampling collecting data for each variable studied using a questionnaire with a Rating scale. The analysis technique uses simple regression and multiple regression. The results showed that; there was a positive relationship between team learning and innovative work behavior (ry1 = 0.398, ρ0,01), there was a positive relationship between knowledge sharing and innovative work behavior (ry2 = 0.687, ρ0,01), and there was a positive and very significant relationship between team learning and knowledge sharing with innovative work behavior (ry12 = 0.671, ρ0,01). Thus, it can be concluded that team learning and knowledge sharing are able to improve innovative work behavior either partially or together.